Systemic Conditions of Political Aggression (SCOPA) Project, 1955-1964 - Feierabend, Ivo ([Verlag nicht ermittelbar], 1984)
This study contains data on 35,000 worldwide domestic conflict events in the period 1955-1964. The events fall under two broad categories: (1) turmoil initiated by members of the general populace and directed either against the government or against other persons or groups within the society, and (2) coercion and conciliation initiated by officeholders and directed toward other members or branches of the government. A subset of events in both categories is designated as minority group tensions. Variables include the legal status of the nation, type of event, type of group, issues involved, event's location, duration of event, number of participants, amount of violence, number of people arrested, injured, or killed, and the level of repressive force. A summary scale was developed to indicate the intensity of the event.